Idealising the System: The Machine as a Tool of Capitalist Control and Intellectual Conformity in E.M. Forster’s The Machine Stops - Nabiha Nisar (`, 2025)
This research paper aims to provide a profound commentary on how capitalist control structures can be found beneath the dystopian surface of E.M. Forster’s The Machine Stops, which offers a prescient critique of technological advancement. This essay examines how the Machine operates as a hegemonic force that upholds social order and intellectual conformity through mechanisms remarkably reminiscent of those found in capitalist ideology, rather than just as a convenient tool. This study uses a Marxist perspective to analyse how the machine, which automates production, controls thought, and commodifies human experience, represents both the ideological superstructure and the economic base. The story shows how the citizens fall victim to a kind of false consciousness, mistaking conformity for wisdom and dependence for advancement, as a result of their alienation from nature, human contact, and real labour. By examining the machine as a system of ideological reproduction and a symbol of capitalist control, this paper contends that Forster’s work foreshadows the social and psychological effects of uncontrolled technological capitalism. The Machine Stops is ultimately a warning against technological determinism as well as a foreboding critique of a society in which the system, rather than the individual, becomes the object of worship.